2014
DOI: 10.1021/ac501801m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Dimensional Profiling of Highly Purified Extracellular Vesicles by Fluorescence Fluctuation Spectroscopy

Abstract: Cells secrete extracellular vesicles (EVs) into their microenvironment that act as mediators of intercellular communication under physiological conditions and in this context also actively participate in spreading various diseases. Large efforts are currently made to produce reliable EV samples and to develop, improve, and standardize techniques allowing their biophysical characterization. Here, we used ultrafiltration and size-exclusion chromatography for the isolation and a model-free fluorescence fluctuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 29 publications
5
58
0
Order By: Relevance
“…Single particle analysis techniques that do not provide high-resolution images but calculate biophysical parameters of single EVs can be used to quantify a large number of EVs with a higher statistical power than many single-EV techniques. For instance, size can be inferred from particle displacement pattern by nanoparticle tracking analysis [184,185,250]; light scattering and/or fluorescence detection in high resolution flow cytometry [251][252][253][254][255]; multi-angle light scattering combined with asymmetric flow field-flow fractionation (AF4-MALS) [256]; displacement of an electrical field in tunable resistive pulse sensing-based devices; or fluorescence correlation spectroscopy (FCS) [257][258][259]. Chemical composition can be evaluated by Raman tweezers microscopy [251][252][253].…”
Section: Single Vesicle Analysismentioning
confidence: 99%
“…Single particle analysis techniques that do not provide high-resolution images but calculate biophysical parameters of single EVs can be used to quantify a large number of EVs with a higher statistical power than many single-EV techniques. For instance, size can be inferred from particle displacement pattern by nanoparticle tracking analysis [184,185,250]; light scattering and/or fluorescence detection in high resolution flow cytometry [251][252][253][254][255]; multi-angle light scattering combined with asymmetric flow field-flow fractionation (AF4-MALS) [256]; displacement of an electrical field in tunable resistive pulse sensing-based devices; or fluorescence correlation spectroscopy (FCS) [257][258][259]. Chemical composition can be evaluated by Raman tweezers microscopy [251][252][253].…”
Section: Single Vesicle Analysismentioning
confidence: 99%
“…This feature drives the detection limit under 50 nm, and is less prone to erroneous results in the presence of larger particles [79,80]. Recently, Wyss et al in an elegant study showed for the first time that this technique can be used to determine not only the average parameters such as concentration and size of the particles, but also, the number of bound antibodies (anti-CD63) per individual EVs, which corresponds to the relative expression level of a particular membrane receptor [81]. …”
Section: Flow Cytometry and Related Methodsmentioning
confidence: 99%
“…13,14) Although our method has not been universally recognized for purifying exosomes, Wyss et al recently showed that ultrafiltration and size-exclusion are valid methodologies for intact exosome purification. 15) Because exosomal marker proteins (Alix, tsg101, hsp70 and CD63) were detected in both samples by Western blot analysis, we designated the vesicles as exosomes I and II. Exosome I was derived from the void fraction from the column.…”
mentioning
confidence: 99%